Pemanfaatan Aplikasi E-Commerce Menggunakan Metode Agile pada Usaha Kue dan Makanan Minang Kreatif - Heru Saputra; Ilfa Stephane; Ade Titin Sumarni; Monanda Rio Meta; Muhammad Alfarel (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2024)
E-commerce, or electronic commerce, refers to the buying and selling of products or services through electronic networks such as the internet, which has opened up vast market potential and increased efficiency for UMKM in Indonesia. In this study, an e-commerce application was developed for Usaha Kue dan Makanan Minang Kreatif using the agile methodology. This method was chosen for its adaptability to changing market needs. Data collection was conducted through interviews, observations, and literature studies. The results indicate that the implementation of e-commerce can enhance operational efficiency and market reach. The developed application facilitates the sales and marketing processes, helping Usaha Kue dan Makanan Minang Kreatif to adapt to digital technology, increase revenue, and improve product visibility. Thus, e-commerce emerges as a potential solution to overcome various challenges faced by UMKM and contributes to local economic growth.